Rapunzel's perfect pony - Clauss, Lauren; Disney Storybook Artists (New York Random House, 2020)
Welcome to the magical world of Palace Pets, where each Disney Princess has a furry pet to love and care for! Blondie loves being Princess Rapunzel's royal pony. What will happen when a new pet moves into the castle? Young readers and Disney Princess Palace Pets fans ages 3 to 5 will love this book, which is full of sweet, cuddly pets--and 30+ stickers! Step 1 readers feature big type and easy words. Rhymes and rhythmic text paired with picture clues help children decode the story. For children who know the alphabet and are eager to begin reading
At head of title: Disney princess, Palace pets
English Stories
Preschool-Kindergarten
Keywords: Pets -- Juvenile fiction; Ponies -- Juvenile fiction; Princesses -- Juvenile fiction; Pets -- Fiction; Ponies -- Fiction; Princesses -- Fiction; Animaux familiers -- Romans, nouvelles, etc. pour la jeunesse; Princesses -- Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION -- Animals -- Baby Animals; JUVENILE FICTION -- Media Tie-In; Pets; Ponies; Princesses; Easy readers; Fiction; High interest-low vocabulary books; Juvenile works; Lectures et morceaux choisis; Readers (Publications); Readers (Publications); readers